Zinc inhibition of cell division : its relevance to cancer cells and possible mechanism of action - Skeef, Noel Samuel (Rhodes University, Faculty of Science, Department of Chemistry and Biochemistry, 1989)
A description of two techniques used extensively in this study namely cell counting with a "cell counting plate" and argentation TLC for the separation of Ï‰ -6 -fatty acids is given. Zn supplementation into GM of two malignant (BL-6 and Hep- 350) and a non-malignant (LLC-MK) cell line/s resulted in an increased uptake of Zn by the cells and progressively suppressed proliferation of particularly the malignant cells. Zn chelation by EDTA suppressed in vitro proliferation of all 3 cell line, this effect being more pronounced in the malignant cells. A dietary Zn deficiency resulted in alopecia in mice and both a dietary Zn deficiency and Zn excess reduced growth of BL-6 tumours implanted subcutaneously in mice. Zn supplementation into GM progressively increased the uptake of [1-Â¹â ´C]-LA by BL-6 and LLC-MK cells but had a very slight though irregular effect on this parameter in the Hep- 350 cells. Zn supplementation also stimulated desaturase activity in the BL-6 cells. These results suggested that there are select cell lines whose Î”â ¶-desaturase activity responds positively to Zn supplementation (e.g. the BL-6 cells). Delta-6-desaturase activity was also assayed in microsome preparations from different tissues. No enzyme activity was detected in the microsomes prepared from the BL-6 tumours. There was no significant effect with the addition of Zn or EDTA, on Î”â ¶-desaturase activity of the regenerating liver microsomes. In the resting liver microsomes this enzyme activity was reduced only when EDTA and Zn were added together and when EDTA was added to the reaction medium as well as to the microsome preparations 2 hr before the enzyme activity assay was initiated. The results of these experiments suggested that the Î”â ¶-desaturase enzyme in the microsome preparations may have had an adequate amount of Zn with further additions having no stimulatory effect on the enzyme. Two independent mechanisms of control of cell proliferation by low and high Zn are suggested to operate.
Keywords: Cell division; Cancer cells -- Growth -- Regulation; Zinc in the body; Zinc -- Physiological effect; Cancer -- Research